Factors affecting the poor performance of form six Bidayuh students in MUET exam / Menon Maton - Maton, Menon (2012)
The study seeks to achieve three main objectives namely, to determine the students’ level of attitudes and motivations towards learning English, to explore the students’ views on factors that contribute to their poor performance in MUET Exam and to investigate how Bidayuh students cope with the preparation for the MUET Exam. The study involved Form Six Bidayuh students of SMK Tun Abdul Razak, situated about 40 kilometres from Kuching, the capital city of Sarawak. To assess the students’ attitudes and motivations, a questionnaire was adapted from Gardner's Attitude/Motivation Test Battery (AMTB) (Gardner, 1985). The questionnaire is comprised of 104 items representing 12 main domains. The results of the questionnaire were analysed using SPSS for descriptive statistics for mean scores indicated that the students were ‘not sure’ of their attitudes and motivations, scoring within the 4.00 range. This could explain why the Bidayuh students had poor performance in the MUET Test. Quite contrary however was the results of the interview which indicated that the students were in favour of English and positive towards learning it. The students in the semi-structured interview also revealed that they did not prepare on their own for the MUET Exam and put heavy reliance on the classes only which proved insufficient.